Stakeholder’s Perception on Sustainable Business Practices for Transportation Infrastructure Development in Sarawak - AGILARAJAN, SELVARAJAH (UNIVERSITI MALAYSIA SARAWAK, 2024)
As Sarawak prospers economically, the challenges in achieving its sustainability goals exist, especially when it comes to integrating sustainable business practices (SBP) into sustainable transportation infrastructure development (STID). Therefore, the need of investigation stakeholder perceptions of both on opportunities and challenges of integrating SBP into STID and its impact to STID arises. This research seeks to gain stakeholder perspectives in implementation of SBP within Sarawak's transportation infrastructure sector. This study employed qualitative research design guided by phenomenology approach which consisted of semi-structured interviews with seven key stakeholders. This provided a rich depth of insight into their views and experiences. The interviews revealed a widespread acknowledgement of the importance of sustainability, yet significant challenges which includes lack of regulatory support, scarce financial resources and limited awareness about sustainable practices which remains as a challenge in full adoption of SBP in STID. The conclusions drawn from this research show that for effective STID in Sarawak, greater attention needs to be paid on strengthening stakeholder engagement and refining policy frameworks that support sustainability initiatives. These findings provide vital guidance for future policy and strategy decisions by government and business leaders in Sarawak seeking to promote sustainable transportation projects. Addressing the obstacles to sustainability will not only smoother implementation but will also contribute to meeting Sarawak’s wider economic, environmental, and social goals.